2016
DOI: 10.1590/s0100-204x2016000700005
|View full text |Cite
|
Sign up to set email alerts
|

Qualidade pós-colheita de banana 'Maçã' tratada com ácido giberélico avaliada por redes neurais artificiais

Abstract: Resumo -O objetivo deste trabalho foi avaliar o efeito de doses de ácido giberélico (GA 3 ) sobre a extensão da vida pós-colheita em banana 'Maçã' e a aplicabilidade de uso de redes neurais artificiais. Utilizou-se o delineamento inteiramente casualizado, em arranjo de parcelas subdivididas, com cinco doses de GA 3 , nas parcelas, e tempos de avaliação, nas subparcelas, e quatro repetições, com um buquê de três frutos por unidade amostral. Os frutos, colhidos com a casca totalmente verde, foram imersos por 10 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 18 publications
0
3
0
2
Order By: Relevance
“…The artificial neural networks (ANN) is a successful tool to describe, substantiate, and elucidate high-complexity issues in the field of modeling Azevedo et al, 2015;Brasileiro et al, 2015;Soares et al, 2015;Aquino et al, 2016aAquino et al, , 2016bAzevedo et al, 2017). Thus, the use of ANN in agronomic modeling for the cactus pear crop can be efficient for predicting yield.…”
Section: Introductionmentioning
confidence: 99%
“…The artificial neural networks (ANN) is a successful tool to describe, substantiate, and elucidate high-complexity issues in the field of modeling Azevedo et al, 2015;Brasileiro et al, 2015;Soares et al, 2015;Aquino et al, 2016aAquino et al, , 2016bAzevedo et al, 2017). Thus, the use of ANN in agronomic modeling for the cactus pear crop can be efficient for predicting yield.…”
Section: Introductionmentioning
confidence: 99%
“…Ainda estudando a qualidade pós-colheita de banana 'Prata Rio' refrigerada, Santos (2017) observou perda de massa de 9,37% no 30° dia de armazenamento à temperatura de 13 °C. A mudança de cor da casca do estádio de cor 1 (casca totalmente verde) para 6 (casca totalmente amarela) observada na Figura 2, é caracterizada pelo decréscimo dos teores de clorofila, o que evidencia o aparecimento da coloração amarela (Aquino et al, 2016;Silva Campelo et al, 2020). A aparência externa é uma variável de importância em frutos, pois ela define a intenção de compra pelo consumidor.…”
Section: Características Físicasunclassified
“…It was observed that the modeling by Artificial Neural Network was efficient in adjusting the obtained data, having good correlation coefficients (with the exception of crude fiber analysis), and low values of relative mean error (P) and standard error of the estimate (SE). This tool has been used by many authors because of their effectiveness in data fitting [8,25,26]. It can be noticed that the modeling by Artificial Neural Network was also efficient in adjusting the data obtained for the milk analysis, having good correlation coefficients, and low values of mean relative error (P) and standard error of the estimate (SE).…”
Section: Kinetic Modelingmentioning
confidence: 99%